Study on the potential capacity of cake fertilizer agricultural solid emission reduction and soil improvement based on CiteSpace - Fu, Yuliang; Li, Gang; Wang, Songlin; Dai, Zhiguang; Zhang, Xiaoyuan (Frontiers in Plant Science, 2025)
IntroductionThe goal was to gain a comprehensive understanding of the current research status, hotspots and cutting-edge dynamics in the field of cake fertilizer application in agriculture at home and abroad from 2000 to 2024.MethodsThe study employed the bibliometric analysis method and CiteSpace visualisation software to investigate the research results of the field of cake fertilizer agriculture in greenhouse gases and soil improvement included in the Core Collection Database of Web of Science.ResultsThe findings of the keyword analysis, collaborative network analysis, and publication count analysis demonstrated that (1) "The number of related literatures was small and in its infancy before 2007,accounting for 17% of the total number of publications; the slow growth phase was from 2008-2016, accounting for 39% of the total number of publications(with a growth rate of 1.65%); and the rapid increase phase was after 2017-2023, accounting for 39% of the total number of publications(with a growth rate of 3.89%). (2) India ranked first in terms of the number of publications, and China ranked second in terms of the number of publications, but China was first in terms of intermediary centrality, and the authors were all loosely distributed, choosing to publish their research results in international journals with an impact factor of greater than 2 in the field of agriculture. (3) Universities are the primary source of research findings in this field among the issuing institutions. (4) The research hotspots include nitrogen, soil, growth, yield, manure, fertilizer, quality, management; The research themes with the greatest number of keywords are "bag filiter," and "bacillus sp " has the highest profile value; The development trends are as follows: prior to 2016, the fertilizer program studied various organic fertilizers in combination with chemical fertilizers or different types of organic fertilizers to explore the impact on crop yields; subsequent to 2016, the fertilizer program studied cake fertilizers with new materials to evaluate the impact on crop yield quality and soil fertility. Going forward, the emphasis should be on blending environmentally friendly components with cake fertilizers and carrying out comprehensive studies on soil enhancement and greenhouse gas mitigation strategies.DiscussionThis study offers new insights and ideas on the future research direction and development potential of cake fertilizer in agricultural greenhouse gas emission reduction and soil improvement. It also serves as a valuable reference for understanding the development trend of cake fertilizer application in agriculture from 2000 to 2023.